Investigation into recurring military helicopter landing gear failure. (May 2016) - Krstic, Branimir; Rebhi, Lamine; Trifkovic, Dragan; Khettou, Nabil; Dodic, Marjan; Peric, Sreten; Milovancevic, Milorad
Abstract: The skid landing gear of a military helicopter failed while the helicopter was moored on the ground at the airport. The rear cross tube of the landing gear assembly was found fractured into two separated pieces. The fracture occurred in the right flange of the rear cross tube, where a connection with the spring tube is established using a clamp. The initial visual inspection of the fracture zone revealed a presence of heavy corrosion and significant damage of the anti-corrosion protective layer on the outer surface of the flange of the rear cross tube. Fractographic analysis highlighted corrosion as the main cause of the failure. Evidence was found to show that the fracture was initiated from corrosion pits located on the exterior, underside of the cylindrical part of the flange. Metallographic examination discovered corrosion pits with micro cracks and multiple branched secondary cracks in the crack origin area, indicating the occurrence of stress corrosion cracking. Chemical analysis of the corrosion deposits showed the presence of sodium, chlorine, calcium and sulfur. The stress analysis of the helicopter landing gear assembly, carried out by means of finite element method, confirmed that the crack origin was located at the area with the maximum tensile stress in the flange. Highlights: The helicopter landing gear failed while helicopter was moored on the ground. The rear cross tube of the landing gear was made of martensitic alloy steel. The SCC cracks initiated from corrosion pits were located on the underside of the flange. The FE analysis showed the maximum tensile stress in the crack origin area.